2011
DOI: 10.1002/crat.201100080
|View full text |Cite
|
Sign up to set email alerts
|

FTIR, powder XRD, TEM and dielectric studies of pure and zinc doped nano‐hydroxyapatite

Abstract: Hydroxyapatite, Ca 10 (PO 4 ) 6 (OH) 2 or HAP, is an important bio-material, which is having application in bone implants and dentistry. In the present study, zinc doped nano-hydroxyapatite (Zn-HAP) was synthesized via chemical precipitation route using surfactant mediated approach. The doping of zinc was confirmed by EDAX. The powder X-ray diffraction (XRD) pattern revealed the typical hydroxyapatite pattern with broadening and extra peaks were observed for higher concentration. The average crystallite size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 65 publications
7
37
1
Order By: Relevance
“…Furthermore, the band from around 1036 cm −1 is associated with the ] 3 bending mode [21,26]. There is also another band attributed to the HPO 4 2− found in the spectral range 870-880 cm −1 [21,24]. However, this one is almost impossible to distinguish due to the fact that it overlaps another vibrational band attributed to the CO 3 2− group [26].…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, the band from around 1036 cm −1 is associated with the ] 3 bending mode [21,26]. There is also another band attributed to the HPO 4 2− found in the spectral range 870-880 cm −1 [21,24]. However, this one is almost impossible to distinguish due to the fact that it overlaps another vibrational band attributed to the CO 3 2− group [26].…”
Section: Resultsmentioning
confidence: 81%
“…This effect was also found for the Zn-doped hydroxyapatite coatings [30]. Tank et al [30] explained this effect as one in which stable interstitial protons form due to the attachment of oxygen of O-H or PO 4 3− groups, leading to the formation of water or HPO 4 2− . Han et al reported that the OH − groups found between 3600 and 3300 cm −1 can be a sign of the presence of the HAP phase [31].…”
Section: Morphologymentioning
confidence: 83%
“…In the case of doped coatings, it will be a competition between Mg 2+ and Ca 2+ to bond with anions, leading to a deficiency of Ca and a presence of water, and HPO4 2− is predicted. This effect was also found for the Zn-doped hydroxyapatite coatings [30]. Tank et al [30] explained this effect as one in which stable interstitial protons form due to the attachment of oxygen of O-H or PO4 3− groups, leading to the formation of water or HPO4 2− .…”
Section: Chemical Binding and Elemental Compositionmentioning
confidence: 83%
“…Hydroxyapatite, Ca 10 (PO 4 ) 6 (OH) 2 , (HA) is a bioceramic material, which constitutes 65% of the human bone mineral component [1]. The trivalent europium ion has been used as a luminescent probe in the investigation of crystallographic structure of activator centers, as well as a tool to probe the local symmetry and occupancy of cationic sites in apatite structures [2].…”
Section: Introductionmentioning
confidence: 99%